Functional Supramolecular Polypeptides Involving pi-pi Stacking and Strong Hydrogen-Bonding Interactions: A Conformation Study toward Carbon Nanotubes (CNTs) Dispersion - Huang, Cheng-Wei; Mohamed, Mohamed Gamal; Zhu, Chao-Yuan; Kuo, Shiao-Wei (My University, 2016)
New supramolecular polypeptides have been prepared through simple ring-opening polymerization and "click" reactions. Postfunctionalization with diaminopyridine (DAP) moieties, capable of multiple hydrogen bonding, was an efficient approach toward forming a-helical-dominant polypeptides. The physically cross-linked networks produced upon self-organization of the DAP units increased the glass transition temperature (T-g) of the polymers and sustained the secondary structures of the polypeptides. Additional thermal responsivity resulted from dynamic noncovalent bonding on the polymer side chains. Molecular recognition through heterocomplementary DAP thymine (T) base pairs was revealed spectroscopically and then used to construct poly(y-propargylL-glutamate)-g-N-(6-acetamidopyridin-2-y1)-11-undecanamide/thyminylpyrene (PPLG-DAP/Py-T) supramolecular complexes. Transmission electron microscopy images revealed that this complex was an efficient dispersant of carbon nanotubes (CNTs). Indeed, it could disperse CNTs in both polar and nonpolar media, the direct result of combining two modes of secondary noncovalent bonding: multiple hydrogen bonding and pi-pi interactions. Furthermore, CNT composites fabricated with biocompatible polymers and high value of T-g should enable the development of bio-inspired carbon nanostructures and lead the way toward their biomedical applications.